Library users’ attitudes towards Virtual Library and Information Services in Ugandan public and private universities - Namugera, Lydia; Bukirwa, Joyce; Okello-Obura, Constant (Library Philosophy and Practice (e-journal), 2023)
Technological advancements, innovations, research, changing user needs, and online education have significantly affected traditional libraries. The 21st-century has engendered library users who seldom visit physical libraries but rely on alternative sources of information like Google from their convenient locations. This implies that for libraries to effectively adapt to the technologically driven academic landscape, adoption of Virtual Library and Information Services (VLIS) is the most feasible approach for them to fulfill their mandate of information provision. However, despite the numerous benefits VLIS offers, such as timely and convenient access to a wide range of current electronic resources, its adoption, implementation and consumption remains limited. This paper gives a report of a study that was conducted to determine the attitude of library users and faculty towards VLIS at Makerere and Uganda Christian University (UCU) libraries. A pragmatic research paradigm with mixed methods approach was adopted to collect data from 394 library users, using a questionnaire while interviews were conducted with 8 library staff. Data were analyzed using the SPSS. Study findings indicated that VLIS is perceived highly in terms of enhancing users’ studies and significance in the core universities tasks. Users’ also exhibited interest in acquiring more VLIS knowledge and demonstrated their appreciation of VLIS. Conversely, users’ in using VLIS was rated poor. Recommendations included modification of the Open Distance and E-learning policies, integration of active links of e-resources in students’ reading lists, a media monitoring room, zero rating on all library websites and incorporation of IL into the university curriculum.